The effects of high-intensity warm-up sets on bench press strength - Mateus de L. Rodrigues; Franciel J. Arantes; João Elias D. Nunes; Frederico B. Lizardo; Guilherme G. de Agostini; Igor M. Mariano; Cristiano L. M. de Barros (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: Movement specific warm-up is a widely accepted practice in the sports environment; however, little is known regarding the ideal intensity of its performance. To verify the effects of adding high-intensity sets to the warm-up on strength, muscular electrical activity, and body temperature in the bench press exercise. Methods: Twelve men (21±1.7 years, 23.9±3.5 kg.m2) were evaluated by a maximal repetition test (1-RM), after which the volunteers performed three procedures: Low-intensity warm-up (LIW), low-intensity warm-up with high-intensity sets (WHI), and no warm-up (CON). Next, they performed maximal isometric voluntary contractions (MIVC) of the chest press to assess the electromyographic activity of the pectoralis major, peak rate of force, development (RFDpeak), and maximum strength (Smax). The skin temperature was evaluated before starting the test. Results: No between-condition differences (p≤0.05) were found for Smax (CON = 320.3±83.8 N; LIW = 300.1±131.6 N, HIW = 327.0±113.9 N; p = 0.689), RFDpeak (CON = 4399±1776 Ns-1; LIW = 3476±1905 Ns-1; HIW = 4715±2184 Ns-1; p = 0.243), skin temperature (CON = 34.0±1.0 °C, LIW = 34.9±0.8 °C, HIW = 34.8±1.1 °C; p = 0.078) or myoelectric activity according to the root mean square index of sternocostal (p = 0.402) and clavicular (p = 0.535) heads, as well as the median frequency data of sternocostal (p = 0.169) and clavicular heads (p = 0.456). Conclusion: In conclusion, the proposed warm-up protocols were not able to modify strength, muscle electrical activity, or skin temperature in the bench press exercise.